2010
DOI: 10.1056/nejmoa1006448
|View full text |Cite|
|
Sign up to set email alerts
|

Anaplastic Lymphoma Kinase Inhibition in Non–Small-Cell Lung Cancer

Abstract: BACKGROUND-Oncogenic fusion genes consisting of EML4 and anaplastic lymphoma kinase (ALK) are present in a subgroup of non-small-cell lung cancers, representing 2 to 7% of such tumors. We explored the therapeutic efficacy of inhibiting ALK in such tumors in an early-phase clinical trial of crizotinib (PF-02341066), an orally available small-molecule inhibitor of the ALK tyrosine kinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

56
2,973
8
37

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 4,078 publications
(3,113 citation statements)
references
References 28 publications
56
2,973
8
37
Order By: Relevance
“…In agreement with Albarracin et al, 3 we think that an analytical report completed with a critical evaluation of the results about HER-2 genetic heterogeneity (GH) should be worldwide promoted.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with Albarracin et al, 3 we think that an analytical report completed with a critical evaluation of the results about HER-2 genetic heterogeneity (GH) should be worldwide promoted.…”
supporting
confidence: 89%
“…1,2 These reports coincided with the successful results of the clinical trial that tested targeted therapy with crizotinib in ALK-positive lung cancer. 3 Consequently, two recently published large series of adult RCCs cumulatively identified four new ALK-rearranged tumors. 4,5 Current data, combined from four independent studies during 2010-2012, include six ALKrearranged tumors in a representative cohort of 884 RCCs of main morphologies arising in pediatric and adult patients of diverse ethnicities ( Table 1).…”
mentioning
confidence: 99%
“…30,35,181,215,216 Although other studies have indicated that these findings may reflect testing bias, 217 the documentation of an association between younger patient age and an actionable biomarker is another consideration in selecting patients for testing. The boundary between young and not young is not well defined, however, and a clear evidence-based cutoff for this guideline cannot be established.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…The initial phase I trial of crizotinib, a potent ALK and MET inhibitor, was designed to enroll a series of expanded cohorts at the recommended phase II dose based not on histology per se, but on tumors with proven evidence of ALK or MET activation 64 . Following the discovery of ALK in lung cancer that occurred after the phase I study had begun accrual, the protocol was amended to allow an ALK+ NSCLC cohort to be added.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%